Where is Baby Bear? - Moncure, Jane Belk.; Friedman, Joy (Mankato, MN : Childs World, 2001)
Pedrito opens a word window and plays hide-and-seek with the animals he finds there.
"Un libro sobre hogares de animales"--Cover.
Keywords: Hide-and-seek; Juvenile fiction; Animals -- Habitations; Juvenile fiction; Children's book